2022
DOI: 10.1186/s13034-022-00512-8
|View full text |Cite
|
Sign up to set email alerts
|

Global child and adolescent mental health perspectives: bringing change locally, while thinking globally

Abstract: Child and adolescent mental health (CAMH) are a global priority. Different countries across the globe face unique challenges in CAMH services that are specific to them. However, there are multiple issues that are also similar across countries. These issues have been presented in this commentary from the lens of early career CAMH professionals who are alumni of the Donald J Cohen Fellowship program of the IACAPAP. We also present recommendations that can be implemented locally, namely, how promoting mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Medical doctors, nurses, clinical officers, midwives, psychologists, social workers, and community health workers were among the study participants. The diversity of the HCWs engaging in CAMH research brings together a wide range of skills, experiences, and perspectives, leading to a more integrated and effective approach to addressing CAMH challenges [ 2 , 74 ]. Collaboration of the different cadres of HCWs in addressing CAMH issues has been emphasized, as it can facilitate access to child mental health services [ 28 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical doctors, nurses, clinical officers, midwives, psychologists, social workers, and community health workers were among the study participants. The diversity of the HCWs engaging in CAMH research brings together a wide range of skills, experiences, and perspectives, leading to a more integrated and effective approach to addressing CAMH challenges [ 2 , 74 ]. Collaboration of the different cadres of HCWs in addressing CAMH issues has been emphasized, as it can facilitate access to child mental health services [ 28 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in India, doctors reported feeling unconfident in managing childhood psychiatric illnesses [ 99 ]. The scarcity of providers with specific competencies in CAMH is a global concern [ 100 ], due to the limited focus on CAMH in pre-service education programs and the lack of ongoing professional development opportunities [ 2 , 18 ]. To promote CAMH services and enhance practices and competence, comprehensive training programs that address assessment, management, and referral processes are necessary [ 24 , 75 , 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…63 Conversely, positive mental health can reduce teenage inclusion in ADHD, school refusal, autism spectrum disorder (ASD), learning disorders, bullying and other deviant behaviors. 64 Studies have shown that higher motivation to participate in physical activity is associated with higher scores on positive mental health indicators and lower scores on indicators of mental health problems, 65 and that eight weeks of physical activity can significantly improve adolescent mental health. 66 According to the World Health Organization, adolescents need 1 h of moderate-to-vigorous physical activity per day to promote their physical and mental health.…”
Section: Mental Health Mediates Between Physical Activity and Deviant...mentioning
confidence: 99%
“…They belong to a field that values mentorship (39) more than most-perhaps because mentorship can be conceptualized as development occurring across generations, rather than within individuals. Mentorship initiatives in child and adolescent psychiatry have interconnected not just generations, but medical students across the United States (40), and young scholars around the globe (41,42).…”
Section: Learning In Place: Transition Generativity and Legacymentioning
confidence: 99%